Investigating the Impacts of Biochar Amendment and Soil Compaction on Unsaturated Hydraulic Properties of Silty Sand - Chen, Zhongkui; Kamchoom, Viroon; Chen, Rui; Prasittisopin, Lapyote (My University, 2023)
The application of biochar as an environmentally friendly additive for agricultural soils has recently gained significant attention. However, the influence of biochar addition on unsaturated hydraulic behavior at high suction ranges (i.e., exceeding 100 kPa) remains largely understudied. This study investigates the impact of biochar addition on the unsaturated hydraulic properties of biochar amended soil (BAS). The effects of biochar content, particle size, and soil compaction on the unsaturated hydraulic properties of BAS were also considered. Peanut shell biochar was utilized in this investigation and was amended into a compacted silty sand with distinct particle size groups. Soil water retention curves and unsaturated permeability were measured through a series of evaporation tests. Results demonstrate that the impact of soil compaction on the unsaturated hydraulic properties of BAS diminishes at high suction range, regardless of biochar particle size and content. A high degree of compaction reduces the saturated permeability of BAS by minimising soil macropores. On the other hand, incorporating high biochar contents with fine particles into the soil enhances the reduction of unsaturated permeability and the improvement of water holding capacity, thereby making biochar an effective application in soil for sustainability of the agroecological environment.
Keywords: compacted silty sand; evaporation method; peanut shell biochar; soil water retention curve; unsaturated permeability